Sweden : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation highlights that Sweden's growth is expected to slow in 2019, with material downside risks from the global economy and domestic demand. A data-dependent approach to monetary policy is appropriate. Although underlying inflation is expected to rise gradually, uncertainties around this outlook have widened. Automatic fiscal stabilizers should operate fully, and the surplus should decline to the new medium-term target by 2020. The fiscal surplus is estimated to have declined to just under 1 percent of GDP in 2018. The report also discussed that labor market reforms should enhance employment of migrants and the low skilled. The social partners should update wage formation to reflect structural changes in the Swedish economy. Reforms to improve housing affordability are needed even as macroprudential measures help contain household debt vulnerabilities. The tightening of amortization requirements is well-targeted, and its effectiveness should be monitored. Plans to eliminate rent controls on new construction should be complemented by phasing out controls on existing apartments.